2022
DOI: 10.3390/app12126267
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Markers and Creation of Non-Anthocyanin and Anthocyanin-Rich Broccoli (Brassica oleracea var. italica) Cultivars

Abstract: In broccoli, anthocyanin pigments can be accumulated in the flower bud epidermis, resulting in a purple-green head. This study aimed to create non-anthocyanin green broccoli varieties and anthocyanin-rich purple broccoli varieties using new F3′H and Pur7.1-K1 molecular markers, respectively. The breeding program started with crosses of the recipient (superior variety and line) LF02 line with the donor line SN60 carrying the recessive allele f3′h and the donor line BT126 carrying the dominant allele Pur7.1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In our transcriptome analysis, one CYP75B/BolC09g064000.2J was among the DEGs that exhibited much higher expressions in the PB767 lines compared with GB767, and qRT-PCR experiments confirmed that the expression level of CYP75B/BolC09g064000.2J was significantly higher in sepals of PB767. Consistent with an earlier study in broccoli [ 45 ], we also identified a 43 bp deletion in the 2nd exon of CYP75B/BolC09g064000.2J in GB767, resulting in an F3′H transcript with a premature stop codon. The nonsense transcripts of F3′H could lead to the reduction in cyanidins, and accordingly, the content of cyanidin-3-O-sophorotrioside in the curds, compared with PB767, decreased dramatically in GB767.…”
Section: Discussionsupporting
confidence: 91%
“…In our transcriptome analysis, one CYP75B/BolC09g064000.2J was among the DEGs that exhibited much higher expressions in the PB767 lines compared with GB767, and qRT-PCR experiments confirmed that the expression level of CYP75B/BolC09g064000.2J was significantly higher in sepals of PB767. Consistent with an earlier study in broccoli [ 45 ], we also identified a 43 bp deletion in the 2nd exon of CYP75B/BolC09g064000.2J in GB767, resulting in an F3′H transcript with a premature stop codon. The nonsense transcripts of F3′H could lead to the reduction in cyanidins, and accordingly, the content of cyanidin-3-O-sophorotrioside in the curds, compared with PB767, decreased dramatically in GB767.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, among 36 characteristics of 111 broccoli varieties, the coefficient of variation of anthocyanin coloration was the highest, indicating a large significant variation with anthocyanin coloration in the materials tested. Richness in anthocyanins has attracted more and more attention as an essential trait in purple broccoli breeding (Liu et al, 2022a). Anthocyanin-rich varieties of broccoli could be used as the primary material for anthocyanin research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the leaf color changes from green to yellow, which weakens the color-masking effect of chlorophyll ( Sun et al., 2020 ). In broccoli, a QTL mapping study indicates that two QTLs named Pur7.1 and Pur9.1 facilitate the biosynthesis of anthocyanin, and induce the purple cauliflower phenotype ( Liu et al., 2022 ). Further, the CRISPR mutation of BolMYB28 increases glucoraphanin content in the leaves ( Kim et al., 2022 ), which induces a healthcare usage of broccoli.…”
Section: Pre-breeding For Other Types Of Terrace Vegetablesmentioning
confidence: 99%